Effects of ramipril on endothelial function and the expression of proinflammatory cytokines and adhesion molecules in young normotensive subjects with successfully repaired coarctation of aorta: a randomized cross-over study. - Brili, S; Tousoulis, D; Antoniades, C; Vasiliadou, C; Karali, M; Papageorgiou, N; Ioakeimidis, N; Marinou, K; Stefanadi, E; Stefanadis, C (2008)
OBJECTIVES: The purpose of this study was to evaluate the effect of ramipril on endothelial function and inflammatory process in a group of normotensive subjects with successfully repaired coarctation of the aorta (SCR). BACKGROUND: Subjects with SCR experience higher long-term cardiovascular risk as a result of the relapse of arterial hypertension or owing to nonreversible structural changes in the pre-coarctation arterial tree. These subjects experience endothelial dysfunction in the right forearm and appear to have elevated levels of proatherogenic inflammatory markers, even in the absence of arterial hypertension. METHODS: Twenty young individuals age 27.3 +/- 2.4 years old with SCR 13.9 +/- 2.2 years previously, received ramipril 5 mg/day for 4 weeks in a randomized, cross-over, controlled trial. Endothelial function was evaluated in the right forearm by gauge-strain plethysmography, and serum levels of interleukin (IL)-1b, IL-6, soluble CD40 ligand (sCD40L), and soluble vascular cell adhesion molecule (sVCAM)-1 were determined by enzyme-linked immunosorbent assay. RESULTS: Ramipril improved endothelial function (p < 0.001) and decreased the expression of proinflammatory cytokine IL-6 (p < 0.05) and sCD40L (p < 0.01). Furthermore, ramipril decreased serum levels of sVCAM-1 (p < 0.01) but failed to affect serum levels of C-reactive protein. These effects were independent of blood pressure lowering. CONCLUSIONS: Ramipril reversed the impaired endothelial function and decreased the expression of proinflammatory cytokine IL-6, sCD40L, and adhesion molecules in normotensive subjects with SCR. These findings imply that ramipril treatment may have antiatherogenic effects in subjects with SCR, even in the absence of arterial hypertension.